Flow of Compressible Fluids through Pipes with constant cross section: Calculation Algorithms for Ideal Gases - Armijo C., Javier (2005)
We are proposing algoritms to solve problems of flow of an ideal gas in a pipe of constant section. With the compressible flow equations we have determined the pressure and velocity profile for both isothermal and adiabatic flow of air and methane.